2013
DOI: 10.20932/barataria.v0i16.74
|View full text |Cite
|
Sign up to set email alerts
|

El hombre unidimensional fragmentado

Abstract: Parafraseamos el título del conocido ensayo de Herbert Marcuse, puesto que la imagen que tradicionalmente se ha generado del hombre, de la masculinidad, ha sido unidimensional. Es decir, el hombre se caracterizaba por unos rasgos y conductas establecidos y afianzados desde tiempos remotos, considerándose todas las demás señas diferenciadoras como meras desviaciones impropias de lo normativo. Pero observaremos que esta realidad incuestionable, tal y como han analizado diversos investigadores a través de lo que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…In this work, we used this information to investigate the star formation activity for cluster galaxies displaying different kinematic behaviors. Our cluster sample agrees with previous results (Rodríguez del Pino et al 2017) showing lower sSFR values compared to the field main sequence of starforming galaxies at intermediate redshift. Furthermore, galaxies classified as irregulars (A 50) display a slightly lower average sSFR value (-0.2 dex) than their regular counterparts (-0.1 dex), although this difference becomes insignificant when taking into account the scatter of our sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this work, we used this information to investigate the star formation activity for cluster galaxies displaying different kinematic behaviors. Our cluster sample agrees with previous results (Rodríguez del Pino et al 2017) showing lower sSFR values compared to the field main sequence of starforming galaxies at intermediate redshift. Furthermore, galaxies classified as irregulars (A 50) display a slightly lower average sSFR value (-0.2 dex) than their regular counterparts (-0.1 dex), although this difference becomes insignificant when taking into account the scatter of our sample.…”
Section: Discussionsupporting
confidence: 92%
“…Dense environments accelerate and strengthen the quenching of star formation in galaxies (Maier et al 2016, Rodríguez del Pino et al 2017 and their morphological transformation (Kuchner et al 2017). In this work, we used this information to investigate the star formation activity for cluster galaxies displaying different kinematic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown evidence that at a fixed stellar mass, star-formation rates of galaxies in dense environments are skewed to lower values than in the general field (e.g. Koopmann & Kenney 2004a;Poggianti et al 2008;Gallazzi et al 2009;Wolf et al 2009;Finn et al 2010;Vulcani et al 2010;Haines et al 2013;Lin et al 2014;Taranu et al 2014;Rodríguez del Pino et al 2017). This would imply that there are environmental processes at work during the several Gyrs after infall.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent mechanisms, one related to stellar mass and another related to environment, have been proposed to explain this transition, generally called as "quenching", for local galaxies (Peng et al 2010;. In this regard, there would be a "environmental quenching" driven by galactic over-density (e. g., Hirschmann et al 2014;Penny et al 2016;Rodríguez del Pino et al 2017), and "mass quenching", where the shut down of star formation occurs on more dynamic processes (e. g., Bluck et al 2014;Fraser-McKelvie et al 2016;Rowlands et al 2018).…”
Section: Introductionmentioning
confidence: 99%